Tendência temporal, espacial e fatores de risco na ocorrência de pneumonia em lactentes de um hospital de referência no município de João Pessoa-PB - Cavalcanti, Allyevison Ulisses Alves (2012)
Each year, about 13 million children under the age of 5 die in the world due to respiratory diseases, mainly pneumonia, which is responsible for about 20 percent of deaths among children under 5 years old. In Brazil, respiratory diseases are responsible for about 10 percent of deaths among infants under 1 year old, and are the first cause of death among children under the age of four. Many factors are associated with the incidence of pneumonia during childhood, such as environmental and socioeconomic factors. In this context, the main goal here is to investigate the temporal tendency and the risk factors associated with the occurrence of pneumonia in children under two years old treated in a large hospital in Joao Pessoa-PB. The data showed seasonality, showing that in the rainy months in the region of Joao Pessoa-PB the number of hospital admittances due to pneumonia increases. The model obtained in the end through logistic regression presented 4 variables as risk factors for hospital admittances due to pneumonia (mother s education level, father s education level, weight of the newborn, and number of pre-natal medical appointments), and 2 variables as protection factors (vaccination and no home agglomeration). In the spatial analysis it was identified a bigger incidence of hospital admittances due to pneumonia in children that live in peripheral neighborhoods, that have a low socio-economic level. The results show that socio-economic factors are determinant in the morbidity and mortality of respiratory diseases during childhood. They show that the treatment of pneumonia during childhood should not be only therapeutic, but mostly a global intervention in the life conditions of the children and their families. The results of this study corroborate previous researches, providing important data for action plans and goals aiming the prevention and control of pneumonia in children.